2017
DOI: 10.1177/0739532917698446
|View full text |Cite
|
Sign up to set email alerts
|

Readers value objectivity over transparency

Abstract: This study explored the effects of objectivity and transparency on perceived news credibility and newsworthiness. Some journalism scholars and practitioners have argued that transparency is replacing objectivity, which has been a dominant standard in traditional journalism. An online experiment (n=222) found that objective articles were rated more credible and more newsworthy than opinionated articles, while non-transparent articles were rated more credible than transparent articles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 19 publications
2
24
1
1
Order By: Relevance
“…This is both a literal and symbolic separation, reinforcing the norm that opinion ought not intrude into news reporting (Thomas, 2018). Accordingly, empirical studies of news content have operationalized objectivity as the absence of opinion (see, e.g., Lawrence, Molyneux, Coddington, & Holton, 2014;Molyneux, 2015;Tandoc, 2018;Tandoc & Thomas, 2017). It follows, then, that fake news producers may seek to take advantage of this journalistic credibility in order to be believed, by putting on a semblance of objectivity.…”
Section: Objectivitymentioning
confidence: 99%
“…This is both a literal and symbolic separation, reinforcing the norm that opinion ought not intrude into news reporting (Thomas, 2018). Accordingly, empirical studies of news content have operationalized objectivity as the absence of opinion (see, e.g., Lawrence, Molyneux, Coddington, & Holton, 2014;Molyneux, 2015;Tandoc, 2018;Tandoc & Thomas, 2017). It follows, then, that fake news producers may seek to take advantage of this journalistic credibility in order to be believed, by putting on a semblance of objectivity.…”
Section: Objectivitymentioning
confidence: 99%
“…Transparency of authorship affects the credibility perceptions of the professional, and any lesser strategy affords risk to that credibility. While research may not have found any significant short-term transparency effects on credibility and trust of news (Karlsson et al, 2014; Tandoc and Thomas, 2017), the long-term effects may be especially problematic in a news media environment riddled with misinformation, trolling and anonymous social media commentators.…”
Section: Resultsmentioning
confidence: 99%
“…Vaikutus voi olla jopa päinvastainen (esim. Smolkin 2006), jos läpinäkyvyyden nimissä esiin tuodut journalistiset käytännöt eivät vastaakaan yleisön odotuksia (Manninen 2020;Tandoc ja Thomas 2017). Kaiken kaikkiaan tähänastisesta tutkimuksesta ei voida kuitenkaan tehdä pitkälle meneviä tai jyrkkiä johtopäätöksiä.…”
Section: Journalistiset Läpinäkyvyyskäytännötunclassified